[Dr. B. S. Medina, Jr. won 3rd place for his novel "Huling Himagsik"] - Medina, Buenaventura S., Jr. (Animo Repository, 1998)
Dr. B. S. Medina, Jr. of the Philippine Languages Dept. (PLD) won 3rd place for his novel Huling Himagsik in the Centennial Literary Contest. The novel revolves around a family's struggle to keep its legacy of dominion over ancestral land. The family's struggle was also the country's fight for freedom from 1898.